Jenis Ikan Yang Tertangkap Di Batang Kuantan Kawasan Wisata Geopark Silokek Sumatera Barat - Mariani, Nur; Widiana, Rina; Abizar, Abizar (CV. ITTC INDONESIA, 2024)
Batang Kuantan is a river that crosses several villages in Sijunjung Regency where the water is murky and has a brownish yellow color. The contamination of Batang Kuantan occurred as a result of the community using the Batang Kuantan river as a place for gold mining using quicksilver (mercury). The use of mercury (Hg) is one of the concerns in gold mining because it is dangerous for health and pollutes the environment. This research aims to determine the types of fish in the Batang Kuantan Geopark Silokek Tourism Area, Sijunjung Regency, West Sumatra and to determine the physico-chemical conditions of the water including temperature, current speed, dissolved oxygen, degree of acidity, total suspended solids, and mercury in the Batang Kuantan area. Silokek Geopark Tourism, Sijunjung Regency, West Sumatra. This research is a descriptive survey method. This research was carried out in October–November 2023 in Batang Kuantan, Silokek Geopark Tourism Area, Sijunjung Regency, West Sumatra and sample identification was carried out at the Laboratory of the Faculty of Science and Technology, PGRI University of West Sumatra and measurements of Total Suspended Solid, Dissolved Oxygen and Mercury were carried out at the Standardization Center Laboratory. and Padang Industrial Services (BSPJI). The results of the research that had been carried out showed that there were 10 types, namely Mystacoleucus marginatus, Barbonymus schwanenfeldii, Rasbora sumatrana, Puntius binotatus, Pangasius lithostoma, Oreochromis niloticus, Pristolepis grootii, Osphonemus gouramy, Pangasius macronema, Pangasius polyuranodon and the results of physico-chemical measurements showed that the water temperature was around 26- 27°C, Current speed ranges from 0.12-0.33 m/s, Degree of Acidity ranges from 8.50-8.72, Dissolved Oxygen Content ranges from 479-7.43 mg/L, Total Suspended Solids ranges from 326-433 mg /L, and mercury is around 0.001 mg/L.